Evaluating Online Courses: How Learners Perceive Language MOOCs - Ye, Zixuan; Luo, Rong (Learning Technologies and Systems, 2021)
Course evaluation is a mirror of the quality of courses. In recent years, Language MOOCs has become an emerging field of online language education. How learners perceive language MOOCs (LMOOCs) and what constitutes their evaluation of these online courses is vital to the development of online foreign language education. The present study investigates the evaluation of China’s LMOOCs from learners’ perspective and reveals existing problems of current LMOOCs. Based on 600 evaluation comments from learners on China’s biggest MOOC platform “icourse”, our study analyzes distinctive features of language MOOCs that impact on learners’ course evaluation and identify key factors in their evaluation. The research findings show that most learners give positive evaluation of LMOOCs in the study. Meanwhile technology and online management are two dimensions that have brought negative evaluation. The results shed light on the status quo of current LMOOCs and expand the scope of course evaluation to the cyberspace.